1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Help regarding a question Parseval's Theorem

  1. Oct 29, 2008 #1


    User Avatar

    1. The problem statement, all variables and given/known data

    The Fourier series for f(x) = x2 over the interval (−1/2, 1/2) is:

    [tex] f(x) = \frac{1}{12}-\frac{1}{\pi^2} (cos 2\pi x - \frac{1}{2^2}cos4\pi x + \frac{1}{3^2}cos6\pi x) ... [/tex]

    Using Parseval's Theorem, show that

    [tex] \sum _{n = 1}^\infty \frac{1}{n^4} = \frac{\pi^4}{90} [/tex]

    2. Relevant equations

    Fourier's Series:

    [tex] f(x) = \frac{1}{2}a_0 + \sum _{n = 1}^\infty a_n cos\frac{2\pi nx}{l} \sum _{n = 1}^\infty b_n sin \frac{2\pi nx}{l}[/tex]

    [tex] a_0 = \frac{1}{l} \int^{\frac{l}{2}}_{\frac{-l}{2}}f(x) dx [/tex]

    [tex] a_n = \frac{1}{l} \int^{\frac{l}{2}}_{\frac{-l}{2}}f(x) cos \frac{2\pi nx}{l} dx [/tex]

    [tex] b_n = \frac{1}{l} \int^{\frac{l}{2}}_{\frac{-l}{2}}f(x) sin \frac{2\pi nx}{l} dx [/tex]

    Parseval's Theorem:

    [tex] \frac{1}{2\pi} \int^{\pi}_{-\pi}f(x)^2 dx = \frac{1}{4}a_0^2 + \frac{1}{2} \sum _{n = 1}^\infty a_n^2 + \frac{1}{2}\sum _{n = 1}^\infty b_n^2 [/tex]

    3. The attempt at a solution

    See I'm not quite sure where to go from here. It says that it is a Fourier series, but it doesn't seem to fit with the definition of Fourier Series I have quoted below?

    Any assitance would be greatly appreciated,

  2. jcsd
  3. Oct 29, 2008 #2


    User Avatar
    Staff Emeritus
    Science Advisor
    Gold Member

    You multiplied the cosine and sine portions of the Fourier series together, they're supposed to be added. At any rate

    For your f(x), a0=1/6 and then you can distribute the [tex]\frac{-1}{\pi^2}[/tex] to calculate the other ai's

    And then the sine component is just all zeroes (so all your bi's will be 0)
  4. Oct 29, 2008 #3


    User Avatar

    So firstly,

    [tex] f(x) = \frac{1}{2}a_0 + \sum _{n = 1}^\infty a_n cos\frac{2\pi nx}{l} + \sum _{n = 1}^\infty b_n sin \frac{2\pi nx}{l} [/tex]


    [tex] a_0 = \frac{1}{6} [/tex]

    As there are no sins, this implies that b_n = 0 (since b_n is the sin component.)
    Multiplying out the brackets:

    [tex] f(x) = \frac{1}{12} - (\frac{1}{\pi^2}cos 2\pi x - \frac{1}{\pi^2}\frac{1}{2^2}cos4\pi x + \frac{1}{\pi^2}\frac{1}{3^2}cos6\pi x ...) [/tex]

    [tex] f(x) = \frac{1}{12} - (\frac{1}{\pi^2}cos 2\pi x - \frac{1}{4\pi^2}cos4\pi x + \frac{1}{9\pi^2}cos6\pi x ...) [/tex]

    So the a_n seems to be an increasing value:

    [tex] a_n = frac{1}{\pi^2}, frac{1}{4\pi^2}, frac{1}{9\pi^2}... [/tex]

    Does this seem okay so far?


Share this great discussion with others via Reddit, Google+, Twitter, or Facebook